THE REALIZATION OF TEACHERS’ LANGUAGE STYLE WITH REFERENCE TO SEX DIFFERENCE IN TEACHING ENGLISH - Megawati Sinaga; Sumarsih Sumarsih; Rahmad Husein (LINGUISTIK TERAPAN, 2019)
The Objectives of this paper are to describe the realization of language styles used by male and female teacher and the reasons of the using those language styles. The subjects were the teachers of SMP Negeri Pancur batu, they were four English teachers, consits of two male teachers and two female teachers. It was qualitative explanative research designs. The researcher observed the teachers while teaching in order to get the teachers language styles taking place during their teaching in the classroom related to the theory of Tannen, who divides the way of communication into six categories; pairs a contrasting use of language by males and females, they are: status versus support, independence versus intimacy, advice versus understanding, information versus feeling, orders versus proposal and conflict versus compromise. .The results of the data analysis showed that the. The language styles of the male and female teacher were different in the way of communication. The realization of language styles by the teachers’ way of speaking  mostly occur in male teachers’ is orders which is 13 utterances (38.2%), then followed by advice which is 11 utterances (32.4%), then continued by information 6 utterences (20,6%) and then conflict 2 utterances (5,9%) and the last is status 1 utterances (2.9%). Female teachers’ way in communication was mostly realized by orders  which is 10 utterances (29.4%), then followed by feeling which is 8 utterances (23.5%), and then continued by understanding which is 7 utternces (20.6%), and then support which is 5 utterances (14.7%), and the last is proposal which is 4 utterances (11.8%). Besides, it can be seen that eventhough Tannen (1992) suggested the orders were categorized for male way’s of speaking , but based on this study, orders were found in the female teachers’ way of speaking. There were 29.4% the utterances realized by orders although that criteria is not classified to female. In fact, those way of speaking were the most used in the female teachers. According to the male and female teachers all the ways of communication are expressed to encourage the students to reach the lesson competencies well.Keywords:English Teachers, Language Styles, Way of communication,